2003
DOI: 10.1017/s003329170300789x
|View full text |Cite
|
Sign up to set email alerts
|

Somatization among older primary care attenders

Abstract: Somatization is common among older primary care attenders and has similar correlates to younger primary care somatizers. Psychological distress among older primary care attenders is associated with frequent attendance. Improved recognition should result in benefits to patients and services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
(54 reference statements)
3
24
1
Order By: Relevance
“…However, the association between somatoform disorders and FA is in keeping with a large body of evidence from elsewhere [20][21][22]. In fact it has recently been suggested that a redrawing of the diagnostic criteria for the category somatoform disorders is needed, focusing on its main attributes: somatic symptoms, excess concern with symptoms and illness and abnormal health care utilization [34].…”
Section: Association Between Psychiatric Disorders and Fa In Family Pmentioning
confidence: 74%
See 2 more Smart Citations
“…However, the association between somatoform disorders and FA is in keeping with a large body of evidence from elsewhere [20][21][22]. In fact it has recently been suggested that a redrawing of the diagnostic criteria for the category somatoform disorders is needed, focusing on its main attributes: somatic symptoms, excess concern with symptoms and illness and abnormal health care utilization [34].…”
Section: Association Between Psychiatric Disorders and Fa In Family Pmentioning
confidence: 74%
“…Few studies have examined the association between FA behavior and a range of psychiatric disorders. Sheehan et al (2003) found an association between somatization and FA in older primary care attenders, controlling for depression and physical illness, neither of which remained significant [20]. The lack of association with depression could be explained by the increased ability of FPs to detect this disorder [31,33] and therefore treat patients in primary care or refer them for specialist care.…”
Section: Association Between Psychiatric Disorders and Fa In Family Pmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Late-life depression is associated with an increased burden of physical symptoms 2 and functional impairment. 3 Depression also impairs one's ability to adhere to self-management regimens (diet, exercise, quitting smoking, taking medication regularly), potentially worsening the course of chronic medical illness.…”
mentioning
confidence: 99%
“…Somatising presentations are common among older primary care attenders (Sheehan et al, 2003) and a 5% proportion of all those referred to a specialised clinic for somatoform disorders was over 65 years of age (Wilkinson et al, 2001). Comorbidity with depressive/anxiety disorders is likely to be the rule.…”
Section: Neglect Of Somatoform Disorders Dear Editormentioning
confidence: 99%